The Tailor of Inverness - Jean Berton (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2025)
Theatre review of Matthew Zajac’s The Tailor of Inverness, directed by Ben Harrison. Three performances at Chambéry’s La Cité des Arts and Savoie Mont-Blanc University on November 20-21-22 2024 (Premiered at the 2008 Edinburgh international Fringe festival). Common thread: ‘A story of journeys’.